Human Capital Attainment and Performance of Small and Medium Scale Industries in Malaysia - Rahmah Ismail (Universitas Islam Indonesia, 2006)
In Malaysia, the small and medium scale industries (SMIs) comprise more than 90 percent of the total establishments in the manufacturing sector. One of the pertinent issues related to industrial development in Malaysia is less competitiveness among the SMIs as compared to the large-scale industries (LSIs). This subsequently leads to lower contribution of the SMIs to the value added of the manufacturing sector. Competitiveness is closely re-lated to human capital possession like education, training and experience among workers in an organization. This paper attempts to examine the impact of human capital variables on SMIs’ output or value added and labor productivity. The analyses will be based on the data of 138 SMIs collected in 1997 through a field survey. The data covers six major industries in SMIs, namely, food and beverage, wood-based, rubber-based, plastic-based, metal-based and electrical electronic. In this survey workers were grouped into various levels of educa-tion to cover the non-schooling, primary, secondary and tertiary education. They were also categorized into five groups to represent professional, technical, administrative and manage-rial, supervisory and production workers. To achieve the objective of this paper, a Cobb-Douglas production function is estimated by incorporating human capital variables as inde-pendent variables in the output, value added and productivity functions. The study shows that year of schooling amongst workers, workers training and job categories have a significant positive relationship with SMIs’ output and value added growth. Capital-labor ratio and tertiary education have a positive impact on the labor productivity growth.Keywords: small and medium scale industry, human capital, labor productivity